Does COVID‐19 contribute to development of neurological disease?. Issue 1 (17th December 2020) - Mahalakshmi, Arehally M.; Ray, Bipul; Tuladhar, Sunanda; Bhat, Abid; Paneyala, Shasthara; Patteswari, Duraisamy; Sakharkar, Meena Kishore; Hamdan, Hamdan; Ojcius, David M.; Bolla, Srinivasa Rao; Essa, Musthafa Mohamed; Chidambaram, Saravana Babu; et al.
Abstract: Background: Although coronavirus disease 2019 (COVID‐19) has been associated primarily with pneumonia, recent data show that the causative agent of COVID‐19, the coronavirus severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), can infect a large number of vital organs beyond the lungs, such as the heart, kidneys, and the brain. Thus, there is evidence showing possible retrograde transmission of the virus from the olfactory epithelium to regions of the brain stem. Methods: This is a literature review article. The research design method is an evidence‐based rapid review. The present discourse aim is first to scrutinize and assess the available literature on COVID‐19 repercussion on the central nervous system (CNS). Standard literature and database searches were implemented, gathered relevant material, and extracted information was then assessed. Results: The angiotensin‐converting enzyme 2 (ACE2) receptors being the receptor for the virus, the threat to the central nervous system is expected. Neurons and glial cells express ACE2 receptors in the CNS, and recent studies suggest that activated glial cells contribute to neuroinflammation and the devastating effects of SARS‐CoV‐2 infection on the CNS. The SARS‐CoV‐2‐induced immune‐mediated demyelinating disease, cerebrovascular damage, neurodegeneration, and depression are some of the neurological complications discussed here. Conclusion: This review correlates present clinical manifestations of COVID‐19 patients with possible neurological consequences in the future, thus preparing healthcare providers for possible future consequences of COVID‐19. Abstract : This review correlates present clinical manifestations of coronavirus disease 2019 patients with possible neurological consequences. Recent studies suggest that activated glial cells contribute to neuroinflammation and the devastating effects of severe acute respiratory syndrome coronavirus 2 infection on the central nervous system.